Ectopic pregnancy in the fallopian tube of the rudimentary horn of uterus unicornis - Abdus-salam, Rukiyat Adeola; Adeoti, Rasheedat O (Nepal Journal of Obstetrics and Gynaecology, 2019)
Ectopic gestation may occur in the fallopian tubes, cervix, ovary or the abdominal cavity. It results from abnormal implantation of the embryo at sites other than the endometrial cavity of the uterus. Congenital anomalies of the fallopian tubes and uterus may predispose to abnormal implantation of the embryo at other sites hence an ectopic gestation results. We describe a rare case of a 30 year old woman with ruptured ectopic gestation located in the fallopian tube of the rudimentary horn of a uterus unicornis. She was evaluated, resuscitated and had a successful surgical intervention.